Advanced Engineering Forum. - Nedelcu, Dumitru (Advanced Engineering Forum, 2020)
The 37th volume of the journal "Advanced Engineering Forum" includes peer-reviewed manuscripts presenting the engineering solutions and research results dealing with contemporary problems in applied materials science, mechanical engineering, building engineering, applied mechanics, power engineering and engineering management. The professionals in various branches of engineering, students as well as scientific investigators workings in the related fields will find this volume of high value. Aluminum Alloys, Attenuation of Heavy Metals, Butt Joint, Cloud Computing, Coconut Husk, Coefficient of Friction (CoF), Composites, Damage Characterization, Detection Methods, Dissimilar Welding, Dynamic Scheduling, Experimental Modal Analysis (EMA)FEM Modeling, Friction Stir Welding, Glaucoma, Heavy Metal Adsorbent, Modal Parameters, Porous Asphalt Pavement, Resource Allocation, Resource Optimization, Resource Priority, Service Level Agreement, Stormwater Runoff, Variational Mode Decomposition, Wear Materials Science, Mechanical Engineering, Bioscience and Medicine.